Structure and Derivatographic Study of Co(II) Complexes of Salicyclic Acid and Thiosalicyclic Acid - Ranjan Jha, Raj (Asian Journal of Chemistry, 2010)
Bis(salicylato) tetraaquo cobalt (II) and bis(thiosalicylate) diaquo cobalt (II) complexes have been prepared by mixing basic cobalt carbonate with salicylic acid and thiosalicylic acid in 1 : 2 molar ratio. The complexes have been characterised by elemental analysis, IR, UV and visible reflectance spectra and derivatograpkic study (DT, DTA and TGA). The structure of bis(salicylato) tetraaquo cobalt(lI) has been also confirmed by X-ray analysis.